Protective Role of Nuclear Factor-Erythroid 2-Related Factor 2 Against Radiation-Induced Lung Injury and Inflammation - Tian, Xiaoli; Wang, Feng; Luo, Yuan; Ma, Shijing; Zhang, Nannan; Sun, Yingming; You, Chengcheng; Tang, Guiliang; Li, Shuying; Gong, Yan; Xie, Conghua (Frontiers in Oncology, 2018)
Radiation-induced lung injury (RILI) is one of the most common and fatal complications of thoracic radiotherapy. Inflammatory cells infiltration, imbalance of inflammatory cytokines and oxidative damage were reported to be involved in the pathological process of RILI, especially in early phase of RILI. Nuclear factor-erythroid 2-related factor 2 (Nrf2) is a key transcriptional regulator of antioxidative cascades, and regulates life span of mice after administration of thoracic irradiation. We investigated the effect of Nrf2 on RILI and inflammation using Nrf2-knockout, Nrf2-overexpression and wild-type mice with or without 15 Gy ionizing radiation to thorax. Our results showed that Nrf2 deficiency aggravated radiation-induced histopathological changes, macrophages and neutrophils infiltration, serum levels of pro-inflammatory cytokines (IL-6, MCP-1, IFN-γ, TNF and IL-12p70), and the levels of peroxidation products in the mouse lung. Moreover, loss of Nrf2 reduced radiation induced serum levels of anti-inflammatory cytokine, IL-10, and antioxidative proteins. While, Nrf2 overexpression significantly alleviated radiation-induced histopathological changes, macrophages and neutrophils infiltration, serum levels of pro-inflammatory cytokines, and the levels of peroxidation products in lung tissues. Nrf2 overexpression increased the serum levels of IL-10 and antioxidative proteins. These results indicated that Nrf2 had a protective role against radiation induced acute lung injury and inflammation, and that antioxidative therapy might be a promising treatment for RILI.